Perceptions of Youth Religious Understanding of Natural Disaster Resistance and Preparedness - ., Ubbadul Adzkiya; Nurdin, Nazar; Fittria, Anis; Nihayah, Ulfatun (KnE Social Sciences, 2023)
Indonesia is a country with the largest Muslim population in the world. In 2010, according to the Central Bureau of Statistics, Indonesia’s population was 237 million, with an average age of 27.2 years. The composition of the population living in villages and cities is quite balanced, but generally they live on the island of Java, which has a population of 57.5%. Of this population, around 32.3 million people live in Central Java, which is known as supermarkets for natural disasters, ranging from earthquakes, fires, tsunamis, floods, landslides, and eruptions. Central Java experiences disasters of land and forest fires every year, extreme weather, drought, infectious diseases, rob, and tornadoes. The paper aims to explore the religious understanding of young people toward natural disaster resilience and preparedness. This study found that religious understanding generally does not affect Muslim youth regarding resilience and preparedness when facing natural disasters. Young people understand disaster risk and utilize technology to regularly monitor disaster situations. However, the attitude of young Muslims regarding resilience and preparedness is relatively worrying. This study provides an empirical basis for efforts to increase disaster-resilient awareness, especially for youth living in Muslim-majority countries. Keywords: perceptions, youth religious, natural disaster resistance